The Effect of Market Shere and Bank Characteristics on Profitability Bank - Sukirno, Sukirno; Hudin, Muhammad Nurhaula (Universitas Serang Raya, 2023)
Managerial Efficiency Theory of Profit explains that companies that are managed efficiently will earn profits above the average normal profit. This study aims to test this theory through the influence of Loan to Deposit Ratio (LDR), Market Shere and Operational Cost-Operating Income (BOPO) on Return On Assets (ROA) of Conventional Banks in Indonesia which are listed on the Indonesia Stock Exchange for the 2013-2017 period. By using a purposive technique, there were 8 sample companies according to the criteria for research needs and as many as 40 observational data for 5 years of observation. The research method uses a quantitative approach with multiple regression analysis tools. The results of this study prove partially that Market Shere and LDR have a positive effect and BOPO has a negative effect on ROA, while simultaneously Market Shere, LDR and BOPO have a significant effect on ROA